2022
DOI: 10.17221/335/2021-pse
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the root traits of summer maize to improve nutrient uptake and utilisation through rational application of urea ammonium nitrate solution

Abstract: The production of summer maize is greatly affected by nitrogen (N) sources through regulating root growth and distribution. Four N treatments in the field experiment were designed as UAN (urea ammonium nitrate solution was applied under traditional side-dressing method), urea (urea was applied under traditional side-dressing method), UWFI (UAN was applied underwater and fertiliser integration technology) and CK (no N applied). The results showed that the root length density, surface area density and volume of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…These results were consistent with the previous study (P. Wang et al., 2010). The main depth of root water uptake in EM under different irrigation treatments was from 0‐ to 60‐cm layer, which confirmed that the root distribution of EM was shallow because the roots shrank more at the R6 stage compared with LM (Z. Ma et al., 2022). Irrigation influenced crop root systems significantly, resulting in different water absorption depths for plants.…”
Section: Resultsmentioning
confidence: 59%
“…These results were consistent with the previous study (P. Wang et al., 2010). The main depth of root water uptake in EM under different irrigation treatments was from 0‐ to 60‐cm layer, which confirmed that the root distribution of EM was shallow because the roots shrank more at the R6 stage compared with LM (Z. Ma et al., 2022). Irrigation influenced crop root systems significantly, resulting in different water absorption depths for plants.…”
Section: Resultsmentioning
confidence: 59%
“…In agroecosystems, root length, root surface area, root biomass, and other indicators are widely considered important factors that determine nitrogen absorption and utilization in the soil by crops. With the continuous development of intensive and diversified planting, the interactions between roots have become increasingly complex ( Ma et al., 2022 ). In wide-and narrow-row cropping systems, changing the position of nitrogen application is particularly prominent in regulating plant growth and root distribution patterns, affecting the dynamic changes and competitive relationships of the plant population ( Li et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, field experiments showed that, in a wide-and narrowrow planting system, the application of wide-row nitrogen had obvious positive effects on increasing total root biomass, total root surface area, and root length compared to those in narrow-row planting systems, especially under high nitrogen conditions (Figures 4A, D, E). This may be due to the excessive absorption of a small amount of nutrient resources by two adjacent maize roots in narrow-rows, which reduces the concentration of nutrients, thus causing the competition of root with each other, avoiding the space and nutrients occupied by adjacent plant roots, and showing asymmetric growth in space for adjacent plant roots (i.e., the growth of noncompetitive roots is better than that of competitive roots) (Kroon et al, 2009;Wang et al, 2016;Zhang et al, 2022). The application of nitrogen in a wide-row is equivalent to a 'resource pull', which promotes root growth on the non-competitive side, and this 'resource pull' becomes larger with increasing nitrogen application rate (Kembel and Cahill, 2005), increasing the root surface area and length ratio of 0 to2.5 mm in diameter to obtain more nutrients (Supplementary Tables 1, 2).…”
Section: Importance Of the Position Of Nitrogen Application To Root S...mentioning
confidence: 99%